Mapping the Research Landscape of Environmental Management Accounting: A Bibliometric Analysis - Muliyani, Dara (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2026)
Purpose: This study aims to map the academic research landscape of Environmental Management Accounting (EMA) through a bibliometric analysis approach. Grounded in management accounting theory, stakeholder theory, and a sustainability perspective, it emphasizes EMA’s strategic function as a bridge between business performance and environmental accountability. Research Design and Methodology: A quantitative bibliometric analysis was performed using data retrieved from the Scopus database with the search query “Environmental AND Management AND Accounting.” The dataset was analyzed using bibliometric and VOSviewer software to conduct descriptive analysis, co-authorship mapping, co-citation analysis, and keyword co-occurrence analysis. These methods were used to identify dominant research themes, influential authors, and the evolution of themes in EMA scholarship. Findings and Discussion: The findings reveal a rapid growth in EMA publications, with research primarily clustered around three core dimensions: strategic, operational, and economic. The study also highlights that EMA has evolved from a tool for environmental cost tracking into a comprehensive management framework that enhances sustainability practices, operational efficiency, and corporate financial performance. Implications: This study contributes by offering an updated bibliometric mapping of EMA research, providing valuable insights for both academics and practitioners. The results underscore the importance of integrating EMA into corporate sustainability strategies, particularly in the era of digital transformation and the green economy. Future studies are recommended to explore the role of digital technologies in expanding EMA’s implementation and impact.